2021
DOI: 10.1111/desc.13101
|View full text |Cite
|
Sign up to set email alerts
|

I know better! Emerging metacognition allows adolescents to ignore false advice

Abstract: Adolescents aspire for independence. Successful independence means knowing when to rely on one's own knowledge and when to listen to others. A critical prerequisite thus is a well‐developed metacognitive ability to accurately assess the quality of one's own knowledge. Little is known about whether the strive to become an independent decision maker in adolescence is underpinned by the necessary metacognitive skills. Here, we demonstrate that metacognition matures from childhood to adolescence (N = 107) and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…M. Fleming et al, 2014; Maniscalco & Lau, 2012). Based on previous research that included negative meta- d ′ values (Moses-Payne et al, 2021), we report analyses including negative values in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…M. Fleming et al, 2014; Maniscalco & Lau, 2012). Based on previous research that included negative meta- d ′ values (Moses-Payne et al, 2021), we report analyses including negative values in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, we found that memory performance in general (ignoring condition or valence) remained stable across our age range. It might be assumed that memory performance would improve across adolescence and into early adulthood, although, this is not consistently reported in the literature ( Ghetti & Angelini, 2008 , Pauls et al, 2013 ) and social and self-related cognitive processes have shown nonlinear development with age ( Diamond, Carey, & Back, 1983 , Moses-Payne et al, 2021 , Somerville et al, 2013 ). In the case of self-referential memory, the affective and motivational nature of the task might mean that the younger participants in our study were able to reach a better memory performance than under other encoding conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The youngest participants in this study (11-year-olds) had recently transitioned to secondary school. This period of transition is associated with major changes to peer networks ( Brown, 2013 ) as well as pubertal changes ( Schaffhuser, Allemand, & Schwarz, 2017 , Simmons et al, 1979 ) and development in the ability to reflect on the self and others Dumontheil, Apperly, & Blakemore, 2010 , Moses-Payne et al, 2021 , Pfeifer et al, 2009 , Symeonidou et al, 2016 . During this period of transition, adolescents strive to become independent from their parents and discover their own identity ( Koepke & Denissen, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are likely several demographic variables that may affect the efficiency of metamemory processes. Age, for example, is known to affect metamemory, with children having less efficient metamemory because their cognitive system is under development (Moses-Payne et al, 2021 ; Schneider & Löffler, 2016 ). In this research, we explored whether the educational level or the living environment would have any impact on metamemory measures.…”
Section: Discussionmentioning
confidence: 99%